It matters how much it hurts: the role of trauma in community social reconstruction - Čorkalo Biruški, Dinka (2008)
A process of social reconstruction after community exposure to a series of severe and prolonged traumatic experiences is slow, gradual and long lasting. In this paper we explore the role of war traumatic experiences in social recovery. It was assumed that people exposed to more severe traumatic experiences would be less prone to engage actively in the process of social reconstruction as measured by readiness for reconciliation and social distance towards the out-group. War related traumatic and stressful experiences were measured in the sample of 404 Croats and Serbs, citizens of the city of Vukovar, Croatia. Their readiness for reconciliation with “ other side” was also assessed, as well as their readiness to engage in various social contacts with the members of “ enemy” group. As predicted, the more traumatic war related experiences were, the less people were willing to reconcile and less ready to establish closer relations with the members of other group. While less stressful events, although massive, were not related to the readiness for reconciliation, traumatic experiences that included personal losses and/or threat to the life and safety of the participants or their significant others appeared to be a significant factor that prevented people to reconcile. The results showing that trauma is a serious obstacle in restoration of community social relations indicate that there is a need for systematic work with traumatized population in order to facilitate social reconstruction processes. By enabling people to work through their trauma, they are encouraged to integrate their individual and collective experiences, which is a key precondition for a successful individual and social recovery.